ON THE METAMORPHIC MODIFICATION OF CR-SPINEL COMPOSITIONS FROM THE ULTRABASIC ROCKS OF THE PINDOS OPHIOLITE COMPLEX (NW GREECE) - Kapsiotis, A.; Tsikouras, B.; Grammatikopoulos, T.; Karipi, S.; Hatzipanagiotou, H. (Bulletin of the Geological Society of Greece, 2007)
Serpentinites and serpentinised ultramafic rocks from the Pindos ophiolite complex, northwestern Greece, contain Cr-spinel grains that are usually altered. The extent of alteration differs among Cr-spinels and two alteration trends can be distinguished. The most dominant is characterised by Cr-spinel overgrown by Cr-magnetite, while the second shows gradual replacement of Cr-spinel by ferrian chromite locally combined with Cr-magnetite development. Compared to cores, the altered rims are enriched in Fe and show elevated Cr# in both types of alteration, while they are impoverished in Mg and Al only at the second one. The common association of Crmagnetite with serpentine and ferrian chromite with chlorite provides insights to the metamorphic context of their formation through processes that include metasomatism by cation diffusion exchange